The veracious character in selected advertising messages of the most significant banks in Poland during the first stage of the COVID-19 pandemic - Barczyk-Sitkowska, Agnieszka (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
The COVID-19 pandemic has affected advertising communication. One of its effects was a clear reference to the new situation in the content of advertising messages, which can be observed, among others, in banks’ advertisements. In uncertain times the veracity of the message has become particularly important. It consists of, among others, the veracious character. The aim of this article is to characterize the functioning of this type of character in advertising messages of 10 the most significant banks in Poland, which were published on their YouTube channels during the first stage of the pandemic.